: A STUDY OF FUNDAMENTALS AND PRINCIPLES OF SOFTWARE ENGINEERING PROCESS (International Journal of Engineering and Computer Science, 2017)
SSoftware engineering (SE) is the application of a systematic, disciplined, quantifiable approach to the design, development, operation, and maintenance of software and the study of these approaches; that is, the application of engineering  to software. A software development process is concerned primarily with the production aspect of software development as opposed to the technical aspect, such as software tools. These processes exist primarily for supporting the management of software development and are generally skewed toward addressing business concerns. Many software development processes can be run in a similar way to general project management processes. Software process is defined as a set of activities that leads to the production of a software product. Although most of the softwares are custom built, the software engineering market is being gradually shifted towards component based. There is no any ideal approach to a software process that has yet been developed. Some fundamental activities like software specification, design, validation and maintenance are common to all the process activities.